Measuring Spatializing Inequalities of Transport Accessibility and Urban Development Patterns: Focus on Megacity Urbanization, Thailand - Pawinee Iamtrakul; Apinya Padon; Jirawan Klaylee (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
The metropolis of Bangkok is characterized as a primate city because of its role as the capital of Thailand. Its suburbanization spreads to five surrounding provinces. Compared to other provinces in Thailand, it has highly concentrated urban development, without disparity between urban and rural areas. Furthermore, the travel volume in Bangkok and its surrounding areas is the highest in the country, with the majority related to private vehicle usage. This is why Bangkok is ranked as the world’s most congested city. To solve this problem and sustain the urbanization of the capital, it is necessary to understand the urban development patterns in Bangkok and their associated factors in measuring the accessibility of transportation. This research applied factor analysis and cluster analysis to characterize the different district contexts of the Bangkok Metropolitan Region, by selecting the Bangkok Metropolitan Administration (BMA) as the capital city area and Pathum Thani Province as a suburbanized area. Consequently, their transport accessibility could be represented by the level of accessibility in terms of the inequalities in the existing transportation system. Furthermore, by clustering the districts according to their economic and social factors, the causes of these inequalities could be identified by spatializing and geographically highlighting them. These findings should be integrated into the urban planning and development policies to overcome urban development challenges and create a city with more accessible and affordable public transport opportunities.